A 2‐Iodobenzamide Catalyst for Oxidation of Alcohols at Room Temperature. Issue 4 (29th January 2014) - Yakura, Takayuki; Yamada, Akihiro; Noda, Narumi; Fujiwara, Tomoya; Nambu, Hisanori
Abstract A 2‐iodobenzamide catalyst for the oxidation of alcohols was developed. Reaction of alcohols with a catalytic amount of 2‐iodobenzamide in the presence of oxone as a co‐oxidant at room temperature gave the corresponding carbonyl compounds in excellent yields. Primary alcohols were directly converted into the corresponding carboxylic acids, whereas secondary alcohols were oxidized to ketones. A 2‐iodobenzoic acid‐type catalyst for alcohol oxidation at room temperature has not been reported before.